Kewarganegaraan dalam Konteks Hukum Perang: Perlindungan Sipil dan Pengungsi Dizona Konflik - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Rahma Nurwahyuningsih; Adillah Khoirunnisah; Arifah Nur Imamma (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
In the laws of war, citizenship plays an important role in determining the type of protection provided to a person during an armed conflict. Drawing on the principles of international humanitarian law and the latest practices, this article investigates how citizenship status affects the protection of civilians and refugees in conflict zones. The study focuses on the problems faced by people who have lost their citizenship status or are in situations of legal uncertainty during conflict. In addition, the study assesses how effective international conventions such as the Additional Protocol and the Geneva Convention are in protecting civil and refugee rights. This article provides insight into how citizenship affects access by analyzing recent case data, countries' policies, and expert perspectives.This article provides insight into how citizenship affects access to protection and basic rights in conflict zones. The findings aim to offer policy recommendations to improve protection for individuals affected by future armed conflicts.